Beliefs Toward Smoking and COVID-19, and the Pandemic Impact on Smoking Behavior and Quit Intention: Findings from a Community-Based Cross-Sectional Study in Jordan - Ala'a B. Al-Tammemi MD, MPH; Muna Barakat PhD; Dua'a Al Tamimi MSN, BSN; Sami A. Alhallaq MD; Dima M. Al Hasan BSc; Ghena M. Khasawneh MD; Khalil Abu Naqera MD, MPH; Raghad M. Jaradat MD; Fadi W. Farah MD; Hindya O. Al-Maqableh MSc; Alaa Abuawad PhD; Bayan Othman MSc; et al. (SAGE Publishing, 2021)
Background The relationship between smoking and coronavirus disease-2019 (COVID-19) is still topical with mixed epidemiological evidence. However, the pandemic may affect people's beliefs toward smoking as well as their smoking behavior and quit intentions. Considering high smoking rates in Jordan, our current study aimed to assess the following domains in a community-based sample from Jordan: (i) the beliefs that surround smoking/vaping and COVID-19 and (ii) the pandemic impact on smoking behavior and quit intention. Methods A cross-sectional study was conducted in Jordan from March 9 to March 16, 2021, utilizing a web-based structured questionnaire. The questionnaire comprised 13 items on sociodemographic, health, and smoking profiles, 14 items to assess beliefs surrounding COVID-19 and the use of combustible cigarettes (CCs), waterpipe (WP), and electronic cigarettes (ECs), and 12 items to assess the pandemic impact on smoking behavior and quit intention. Results Of 2424 survey respondents who participated in our study, there were 1163 never-smokers, 1044 current smokers, and 217 ex-smokers. The mean age of participants was 35.2 years (SD: 11.06). Most participants have reported anti-smoking beliefs with around 72.9% believed that WP smoking is related to the risk of contracting COVID-19. Also, 71.7% believed that smoking CC may worsen the COVID-19 clinical course, while 74.1% of respondents believed that smoking has no protective effect against COVID-19. During the pandemic, about 28.1% and 19.3% of current smokers reported increased or reduced smoking, respectively. Besides, 459 current smokers have expressed their plans/intention to quit smoking during the pandemic, of whom 27.5% (n = 126) confirmed that the driving force for their decision is a COVID-19-related reason, such as self-protection (n = 123) and protection of family members (n = 121) which were the most cited reasons. Also, around 63 participants have successfully ceased smoking during the pandemic. However, only 22 of them reported that the main driving motivation of their successful quit attempt was the COVID-19 pandemic. Conclusion Most participants' beliefs and attitudes were against smoking during the pandemic. Nevertheless, the double-edged effect of the pandemic on smoking habits should be carefully considered, and reliable anti-smoking measures should be strengthened and sustained in the country.